Study of martensitic transformation in TiNiCuNb shape memory alloys using dynamic mechanical analysis. (September 2018) - Liu, M.Y.; Qi, W.Y.; Tong, Y.X.; Tian, B.; Chen, F.; Li, L.
Abstract: In present work, effect of Nb content on martensitic transformation and damping behavior of (Ti50 Ni38 Cu12 )100-x Nbx (x = 0, 5, 10, 15at.%) shape memory alloys was investigated by means of X-ray diffraction, differential scanning calorimetry and dynamic mechanical analysis. As a result, the transformation sequence of TiNiCuNb alloys is found to be B2→B19→B19′ upon cooling. Two different damping peaks are observed, one is related to B2→B19 transformation and the other one is related to the overlapping of twin relaxation-type and B19→B19′ transformation. With increasing Nb content to 15 at.%, the peak value of damping capacity of B2→B19 transformation slightly decreases. Highlights: B2.→B19→B19′transformation are identified in TiNiCuNb alloys. Two different damping peaks are observed. Peak value of damping capacity of B2.→B19 transformation reduces with increasing Nb content.